COVID-19—A Theory of Autoimmunity Against ACE-2 Explained - McMillan, Philip; Dexhiemer, Thomas; Neubig, Richard R.; Uhal, Bruce D. (Frontiers in Immunology, 2021)
The COVID-19 pandemic caused by the coronavirus SARS-COV-2 has cost many lives worldwide. In dealing with affected patients, the physician is faced with a very unusual pattern of organ damage that is not easily explained on the basis of prior knowledge of viral-induced pathogenesis. It is established that the main receptor for viral entry into tissues is the protein angiotensin-converting enzyme-2 (“ACE-2”, 1). In a recent publication (2), a theory of autoimmunity against ACE-2, and/or against the ACE-2/SARS-COV-2 spike protein complex or degradation products thereof, was proposed as a possible explanation for the unusual pattern of organ damage seen in COVID-19. In the light of more recent information, this manuscript expands on the earlier proposed theory and offers additional, testable hypotheses that could explain both the pattern and timeline of organ dysfunction most often observed in COVID-19.